Interaksi Genetik x Lingkungan dan Stabilitas Komponen Hasil Berbagai Genotipe Kedelai di Provinsi Riau - Aslim Rasyad; , Idwar (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
Genotype by environment (GE) interaction and stability of a trait in any crop plant such as soybean (Glycine max L. Merr.) are very important for plant breeders to develop and evaluate the new cultivars as well as for farmers to plant suitable cultivars for commercial purpose. Crop performances including harvesting date, yield components and grain yield of nine genotypes of soybean were evaluated at three locations with distinct environments in Riau. The data were used to determine GE interaction variance components of the traits and yield stability.  There was significant effect of location on all characters except on grain yield per plot.  The genotypes differed significantly in all yield components and grain yield.  Genotype x environment interaction significantly affected several crop performances such as harvesting date, all yield components and grain yield.  The magnitude of GE interaction variance component was greater than that of location for all traits except the number of seed per plant indicating that most genotypes performed differently across the locations and were not stable with respect to the locations.  Among the nine genotypes, line 19BE and Malabar are classified as stable genotypes and could be grown in wide area of Riau Province, while line 13ED and Kipas Putih produced high grain yield in specific area and could be only grown in Pekanbaru.   Keywords: genotype x environment interaction, yield components, stability, soybean